Positional demands of international rugby union: Evaluation of player actions and movements - Quarrie, K. L.; Hopkins, W. G.; Anthony, M. J.; Gill, N. D. (Journal of Science and Medicine in Sport, 2013)
Abstract: In rugby union, published analyses of actions and movements of players during matches have been limited to small samples of games at regional or national level. Objectives: To analyse movements and activities of players in international rugby union matches with a sample size sufficient to clearly delineate positional roles. Design: Observational study. Methods: Actions of 763 players were coded from video recordings of 90 international matches played by the New Zealand national team (the All Blacks) from 2004 to 2010. Movements of players were coded for 27 of these matches via a semi-automated player-tracking system. Movements and activities of all players from both teams were coded. Results: Cluster analysis of activities and time-motion variables produced five subgroups of forwards (props, hookers, locks, flankers, Number 8 forwards) and five subgroups of backs (scrum-half, fly-half, midfield backs, wings and fullbacks). Forwards sustained much higher contact loads per match than backs, via scrums, rucks, tackles and mauls. Mean distance covered per match ranged from 5400 to 6300 m, with backs generally running further than forwards. There were marked differences between positional groups in the amount of distance covered at various speeds. The amount of play per match varies by position due to differences in rates at which players are substituted. Conclusions: The distance covered by players at relatively fast running speeds (in excess of 5 m s-1) appears to be higher during international matches than when competing at lower levels of the professional game. The specific match demands for positional groups need to be considered when managing player workloads.